Begriffe der strategischen Produktplanung und -entwicklung. Produkt und hybride Leistung - Gräßler, Iris; Ovtcharova, Jivka; Dattner, Michael; Dietert, Tilko; Dietz, Patrick; Elstermann, Matthes; Fayet, Celestin; Hauck, Andreas; Häuser, Frank; Fischer, Holger; Herzog, Michael; Köhler, Christian; et al.

Post-pandemic online mathematics and statistics support: Practitioners’ opinions in Germany and Great Britain & Ireland - Gilbert, H.; Schürmann, M.; Liebendörfer, M.; Lawson, D.; Hodds, M. (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Fachdidaktisches Design von Begründungsvideos im Projekt studiVEMINTvideos - Biehler, Rolf; Guntermann, Dominik; Liebendörfer, Michael; Krämer, Sandra; Schlüter, Sarah (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Erfassung und Vergleich (mathematischer) Eingangsvoraussetzungen angehender Studierender verschiedener mathematikhaltiger Studiengänge - Göller, Robin; Gildehaus, Lara; Liebendörfer, Michael; Besser, Michael (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2021. Beiträge zum gleichnamigen Online-Symposium am 12 November 2021 aus Bochum)

Zu digital - zu viel - zu schwer? Qualitative Einsichten in das Erleben und Handeln von Erstsemester-Studierenden der Mathematik während der Corona-Pandemie - Kempen, Leander; Liebendörfer, Michael (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2021. Beiträge zum gleichnamigen Online-Symposium am 12 November 2021 aus Bochum)

Bearbeitungsmuster von Studierenden im Umgang mit formalen Definitionen im Kontext konstanter Folgen - Schlüter, Sarah; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Förderung prozeduraler Flexibilität durch Lernvideos mit interaktiven Aufgaben - Krämer, Sandra; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Preservice teachers’ mathematics-related values and expectancy in the transition from school to university
Many preservice mathematics teachers lose their motivation during their first year at university. This phenomenon has been repeatedly described in recent years but is not yet fully understood. Since motivation may relate to different objects such as mathematics or teaching, we aim to qualitatively reconstruct different facets of the central motivational constructs of Situated-Expectancy-Value theory (intrinsic value, attainment value, utility value, cost, and expectancy of success) for preservice mathematics teachers. The analysis of longitudinal group interviews of 14 preservice higher-secondary mathematic teachers from a German university revealed different objects of motivation (e.g., teaching mathematics, scientific mathematics, procedural mathematics, or proof-based mathematics) in preservice teachers' values and expectancy of success. Furthermore, relations between those values and expectancy of success were identified that played a significant role in preservice teachers’ motivational development over their first semester (e.g., relations of attainment value for scientific mathematics and psychological cost). Theoretical and practical implications towards a teaching-specific conceptualization of expectancy of success and values and value interventions are being discussed.

Determination of Correlations between Melt Quality and the Screw Performance Index in the Extrusion Process - Trienens, Dorte; Schöppner, Volker; Bunse, Robin (Polymers 2023)

Improvement of a method for the correction of wall slip effects within the rheological measurements of filled rubber compounds - Schöppner, Volker; Kleinschmidt, Dennis (SPE Polymers)

Creating Synthetic Training Data for Machine Vision Quality Gates - Gräßler, Iris; Hieb, Michael; Roesmann, Daniel; Unverzagt, Marc

Dynamic conformity assessment for joining force monitoring using Bayes filters - Butzhammer, Lorenz; Kappe, Fabian; Meschut, Gerson; Hausotte, Tino (Materials Research Proceedings)
Monitoring force-displacement or force-time curves is a widely used quality control technique in the field of mechanical joining. For online monitoring of self-piercing riveting, envelope curves are often used to define a tolerance zone for the measured setting force. However, the measurement uncertainty is typically not considered and the force curve of a joint can be wrongly rated as non-conform due to measurement errors and noise. In this article, we present a method for dynamical online filtering and uncertainty determination for noisy force curves using two types of Bayesian filters. The methodology is based on a Bayesian probability framework using a priori information for the process curve and sensor noise. To investigate the general feasibility of the method, force measurements with different noise levels are simulated and processed. The conformity is further assessed taking the uncertainty of the filtered signal into account. The results show that the Bayes filter technique is principally able to reduce noise for well-known characteristics of the process curve and sensor noise. Advantages over common filtering techniques, especially for experimental conditions with less known characteristics, are still to be verified. The methodology could be used in future for closed-loop controls to adapt process parameters dynamically.

Creating Synthetic Datasets for Deep Learning used in Machine Vision - Gräßler, Iris; Hieb, Michael

CONSIDERING ENGINEERING ACTIVITIES AND PRODUCT CHARACTERISTICS TO ACHIEVE MATERIAL CIRCULARITY BY DESIGN - Gräßler, Iris; Hesse, Philipp (Proceedings of the Design Society)
Abstract To select design guidelines engineers have to identify relevant from a bewildering amount of design guidelines. In this paper, a rule-based method for selecting design guidelines for material circularity selection is presented. For this purpose, a generic Product Life Cycle model is detailed with regard to Multi Material cycles (gPLC-MM). The presented method is divided into four steps. Core of the presented method is the comparison of circular product strategies with product life phases and material recovery processes. Engineering activities and increments of the product architecture are used to identify design guidelines. The results show that through the material circularity-oriented design guideline identification method, the product architecture is designed for different processes and technologies, to recover materials. The method allows engineers to select guidelines in a more targeted and consolidated way in sustainability-friendly product engineering.
Keywords: Sustainability; Circular economy; Conceptual design

Virtual learning environment for teaching the handling of collaborative robots - Gräßler, Iris; Hieb, Michael; Roesmann, Daniel; Unverzagt, Marc; Pottebaum, Jens (SSRN Electronic Journal)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Cloud-Computing für die Verwendung synthetischer Trainingsdaten für Machine Vision Quality Gates - Gräßler, Iris; Hieb, Michael (Automation 2023)

Wall Slip-Free Viscosity Determination of Filled Rubber Compounds Using Steady-State Shear Measurements - Brüning, Florian; Kleinschmidt, Dennis; Petzke, J. (Polymers)

Recycling-Ansatz für mehrkomponentige Kunststoffprodukte durch thermische Verbundtrennung - Schöppner, Volker; Austermeier, Laura; Brüning, Florian; Oldemeier, Jan Philipp; Brandt, O. (EXTRUSION)

Anvil-free ultrasonic welding for welding situations with one sided access - Schöppner, Volker; Arndt, Theresa (76th Annual Assembly of the International Institute of Welding (IIW))

Elastomerrecycling mittels Mikrowellenstrahlung - Brüning, Florian; Kleinschmidt, Dennis; Petzke, J. (Kunststoffland NRW Report)